2022
DOI: 10.1186/s12889-022-12833-6
|View full text |Cite
|
Sign up to set email alerts
|

A nutrition and lifestyle-focused shared medical appointment in a resource-challenged community setting: a mixed-methods study

Abstract: Background In order to address disparities in preventable chronic diseases, we adapted a nutrition and lifestyle-focused shared medical appointment (SMA) program to be delivered in an underserved community setting. The objective was to evaluate a community-based nutrition and lifestyle-focused SMA as it relates to acceptability and health and behavior-related outcomes. Methods A mixed-methods study was performed to evaluate pre-post changes in well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Although this study is unique in exploring the application of SMAs in LMICs, many of the findings are consistent with quantitative research conducted in underserved communities in the US. In particular, some of these studies reported decreased dissatisfaction with diabetes and diabetes distress, as well as improved diabetes-related quality of life, frequency of blood-sugar self-testing, dietary habits, and frequency of exercise among patients participating in SMAs versus those receiving individual care [ 25 , 37 , 38 ]. In other qualitative studies in the US, participants cited a sense of community, improved disease self-management, a sense of empowerment, motivation, increased trust in providers, and gaining knowledge from peers as positive aspects of this model of care delivery [ 18 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study is unique in exploring the application of SMAs in LMICs, many of the findings are consistent with quantitative research conducted in underserved communities in the US. In particular, some of these studies reported decreased dissatisfaction with diabetes and diabetes distress, as well as improved diabetes-related quality of life, frequency of blood-sugar self-testing, dietary habits, and frequency of exercise among patients participating in SMAs versus those receiving individual care [ 25 , 37 , 38 ]. In other qualitative studies in the US, participants cited a sense of community, improved disease self-management, a sense of empowerment, motivation, increased trust in providers, and gaining knowledge from peers as positive aspects of this model of care delivery [ 18 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding healthcare providers, participants in our study highlighted similar benefits of SMAs to those reported in previous qualitative research, such as power-shifting, trust building, better information sharing, improved self-management, peer support, less repetition, and more efficiency than the 1:1 approach [ 18 , 40 ]. One concern raised by practitioners both in our study and in previous SMA interventions, was the administrative workload involved in arranging and facilitating the sessions [ 38 , 40 ]. However, all these comparisons must be considered with caution, as previous SMA interventions were implemented in urban settings in the US and were tailored to those circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…These opportunities include clinical nutrition innovation and dietary strategies for health within existing payor models, such as the interprofessional Culinary Medicine eConsult [ 101 ]. Prior studies describe group medical care to build patient self-efficacy and behavior change in a feasible and creative context [ [102] , [103] , [104] , [105] ]. Efforts should also include the standard integration of referrals to and reimbursement for RDNs to further support and enhance the nutrition conversations with referring clinicians.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%
“…54 This commitment to access can be seen in the creation of multiple patient family advisory councils proposing themes of access, team based care and patient centric communication. 55 The thematic response has been multi‐dimensional: Public health focused shared medical appointment programs for underserved communities 56 ; telemedicine programs promoting mental health 57 ; linkage of thousands to supplies and community resources during the pandemic and federally qualified health center partnerships 58 ; building brand new grocery stores in “food deserts”; internet connectivity in impoverished local neighborhoods. All testament to the continued CCHS focus on access for our most underserved communities.…”
Section: Future Directions/implicationsmentioning
confidence: 99%